Cognitive Stimulation of Elderly Individuals with Instrumental Virtual Reality-Based Activities of Daily Life - Gamito, Pedro (2022)
As the demographic structure in western societies ages, the prevalence and impact of cognitive decline rises. Thus, new solutions to tackle this problem are required. The use of Information and Communication Tech- nologies (ICT)-based cognitive exercises has emerged in the last few decades, though with inconsistent results. Hence, we conducted a pre-post treatment study to further investigate this approach. We designed a set of virtual reality exercises that mimic activities of daily living by which the patient can train different cognitive domains. Twenty-five participants, ages 65–85, underwent 12 training sessions between the pre-treatment and post-treatment assessments. Significant increases were seen between the two assessments for some of the neuropsychological measures: visual memory, attention, and cognitive flexibility. Results also suggest that participants with lower baseline cognitive performance levels improved most after these sessions.